2013
DOI: 10.1590/s0100-204x2013000600002
|View full text |Cite
|
Sign up to set email alerts
|

Parboiled rice whole bran in laying diets for Japanese quails

Abstract: -The objective of this work was to evaluate the effects of parboiled rice whole bran (PRWB) inclusion in laying diets for Japanese quails, on their performance, egg quality, and economic viability. A total of 448 17-week-old quails were weighed and distributed in a completely randomized design with seven treatments and eight replicates of eight birds each. A control diet (no PRWB) and six diets, containing 5, 10, 15, 20, 25, and 30% of PRWB, were tested. The increasing levels of PRWB did not affected nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Table 2 shows the results for feed intake, laying percentage, average egg weight, and feed conversion ratio per dozen eggs and per egg mass. All productive performance variables were similar across treatments (P > 0.05), in line with the observation that, in general, rice by-products have been added in varying levels to poultry diets with satisfactory performance results (BRUM JUNIOR et al, 2007;QUEVEDO FILHO et al, 2013;FARIAS et al, 2014;GOPINGER et al, 2014). Cardoso et al (2011) and Freitas et al (2013) also found no effect of broken rice on feed intake in quails.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Table 2 shows the results for feed intake, laying percentage, average egg weight, and feed conversion ratio per dozen eggs and per egg mass. All productive performance variables were similar across treatments (P > 0.05), in line with the observation that, in general, rice by-products have been added in varying levels to poultry diets with satisfactory performance results (BRUM JUNIOR et al, 2007;QUEVEDO FILHO et al, 2013;FARIAS et al, 2014;GOPINGER et al, 2014). Cardoso et al (2011) and Freitas et al (2013) also found no effect of broken rice on feed intake in quails.…”
Section: Introductionsupporting
confidence: 73%
“…All productive performance variables were similar across treatments (P > 0.05), in line with the observation that, in general, rice by-products have been added in varying levels to poultry diets with satisfactory performance results (BRUM JUNIOR et al, 2007;QUEVEDO FILHO et al, 2013;FARIAS et al, 2014;GOPINGER et al, 2014). Cardoso et al (2011) and Freitas et al (2013) also found no effect of broken rice on feed intake in quails. The difference in metabolizable energy between broken rice and corn for poultry (NARVÁEZ-SOLARTE et al, 2012) was corrected, in this study, in with the addition of oil to the feed, a method that is supported by the studies of Junqueira et al (2009) and Rostagno et al (2011).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Corn is the main energy source in quail diets; this ingredient constitutes 60%-70% of the total cost, and its price is governed by exchange rates and market values. However, alternative ingredients have also been tested depending on availability and market price (Amoah and Martin 2010;Quevedo Filho et al 2013). Whole rice bran (WRB), which is available in rice production regions, is one such ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…The dependence of the poultry sector on soybean meal and corn generates a demand for unconventional, low-cost regional feed sources, which, according to the desired objective, may greatly elevate marginal production gains. Some researchers (FREITAS et al, 2013;QUEVEDO-FILHO et al, 2013;ZARE-SHEIBANI et al, 2015) observed that brown rice bran can be an excellent alternative to be included in the diet of Japanese quail during the starter and laying phases; and for broilers, when aiming to cheapen their feed, replacing corn. Rostagno et al (2017) asserted that rice bran has a standardized ileal digestibility coefficient of amino acids of 70%, on average, and 13.30% CP.…”
Section: Introductionmentioning
confidence: 99%